Method for preparing filler for hemoperfusion device by double biomineralization

The double biomineralization method for hemoperfusion fillers addresses the challenge of enzyme activity loss and thrombosis by forming a biocompatible, efficient, and stable matrix for pathogen removal in hemoperfusion devices.

CN115990462BActive Publication Date: 2024-12-31JIANGSU CHARUI BIOTECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210665953.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-13
Publication Date
2024-12-31
Estimated Expiration
2042-06-13

AI Technical Summary

Technical Problem

Existing hemoperfusion technologies face challenges in flexibly selecting purification factors and maintaining enzyme activity due to chemical modification of adsorbents, which can lead to thrombosis and reduced efficacy.

Method used

A method of preparing fillers for hemoperfusion devices through double biomineralization, involving primary biomineralization with sodium alginate, water-soluble phosphate, and magnetic particles, followed by secondary biomineralization with a silica precursor and acidic buffer solution, to form a biocompatible matrix that retains enzyme activity and provides efficient pathogen removal.

Benefits of technology

The dual biomineralization process enhances enzyme activity retention, forms a loose network for effective pathogen contact, reduces thrombosis risk, and minimizes nonspecific adsorption, resulting in improved purification efficiency and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115990462B_ABST
    Figure CN115990462B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a filler for a blood perfusion device by double biomineralization, the method comprising: (1) primary biomineralization: preparing a mixed solution A containing sodium alginate, water-soluble phosphate, purification factor and magnetic particles, and a solution B containing chitosan and calcium chloride, then dripping the mixed solution A into the solution B to obtain biomineralized magnetic capsule particles; (2) secondary biomineralization: preparing a silica precursor solution and an acidic buffer solution containing glycerol, then mixing the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution, then adding polyallylamine, and reacting to obtain the filler for the blood perfusion device. Compared with the existing macroporous resin and activated carbon for blood perfusion devices, the present invention utilizes biomineralization to physically embed the purification factor in the filler, and during embedding, the corresponding purification factor can be flexibly selected according to different pathogenic factors, and the prepared filler has good biocompatibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of fillers for hemoperfusion devices, and in particular relates to a method for preparing fillers for hemoperfusion devices by double biomineralization. Background Art

[0002] Hemoperfusion is a blood purification technology that introduces the patient's blood into a hemoperfusion device filled with solid adsorbents to remove exogenous or endogenous toxins, drugs or metabolic wastes in the blood that cannot be removed by dialysis through adsorption. It is mainly used to rescue drug and poison poisoning, and can also be used in combination with hemodialysis to remove macromolecular toxins in patients with chronic renal failure who are undergoing maintenance dialysis.

[0003] Solid adsorbents used for hemoperfusion are all polystyrene resins or activated carbon. In order to improve the specific adsorption of pathogenic factors by the adsorbents, purification factors are often fixed on the adsorbents. However, due to the properties of polystyrene resins or activated carbon themselves, the adsorbent substrate needs to be chemically modified before fixing the purification factors. Chemical modification may affect the biocompatibility of the product. If it is not handled properly, thrombosis is likely to form during clinical application, increasing the risk to patients. This makes it difficult to flexibly select the corresponding purification factors according to the pathogenic factors in actual clinical applications.

[0004] Biomineralization is the process by which living organisms manufacture organic-inorganic composite materials by regulating the nucleation, orientation, growth and assembly of inorganic minerals. Since the 1990s, researchers have proposed the concept of biomimetic mineral material synthesis by drawing on the principles of biomineralization. Compared with traditional inorganic minerals, biomimetic mineral materials have been applied to bone tissue, tooth enamel repair, and protective shells of drugs due to their good biocompatibility.

[0005] Patent document CN1986787A discloses a method for biomimetic preparation of silica-alginate microcapsules for immobilizing β-glucuronidase, the method comprising the following steps: (1) Preparation of alginate microcapsules: a β-glucuronidase solution with a concentration of 0.5 mg / ml, a calcium chloride solution with a concentration of 0.6 mol / L and a sodium carboxymethyl cellulose solution with a concentration of 3.0% w / v are uniformly mixed in a volume ratio of 10:8:32, and then added dropwise to a 1.0% w / v sodium alginate solution, stirred for 30 to 60 minutes, diluted with deionized water and filtered, and then immersed in a 0.1 mol / L calcium chloride solution for curing for 10 minutes. Alginate microcapsules with a diameter of 2.5 to 3.5 mm are obtained; (2) protamine is coated on the outer surface of the alginate microcapsules: the alginate microcapsules obtained in step (1) are immersed in 2 to 20 mg / ml protamine sulfate or protamine solution, and filtered after soaking for 30 to 120 minutes to obtain alginate microcapsules coated with protamine; (3) biomimetic synthesis of silica shell under protamine regulation: the microcapsules obtained in step (2) are immersed in 30 to 80 mol / L sodium silicate solution with a pH of 5 to 7, and soaked for 60 to 120 minutes, and filtered to obtain silica-alginate microcapsules. This method effectively solves the swelling problem of alginate microcapsules. However, in the immobilization process, there is inevitably a certain degree of loss of enzyme activity. How to further reduce this loss and retain the activity of the enzyme as much as possible is a problem that needs to be further solved in this field. Summary of the invention

[0006] In order to enable the filler for the liquid perfusion device to flexibly select the required purification factors according to the pathogenic factors while reducing the loss of purification factor activity, the present invention provides a method for preparing the filler for the blood perfusion device by double biomineralization using biomimetic mineralization technology.

[0007] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0008] The method for preparing filler for hemoperfusion device by double biomineralization comprises:

[0009] (1) Primary biomineralization: preparing a mixed solution A containing sodium alginate, water-soluble phosphate, purification factor and magnetic particles, and a solution B containing chitosan and calcium chloride, and then dropping the mixed solution A into the solution B to obtain biomineralized magnetic capsule particles;

[0010] (2) Secondary biomineralization: preparing a silica precursor solution and an acidic buffer solution containing glycerol, then mixing the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution, and then adding polyallylamine to react to obtain the filler for the hemoperfusion device.

[0011] Preferably, in the mixed solution A, the mass ratio of sodium alginate, water-soluble phosphate, purification factor and magnetic particles is 0.1-2:0.1-2:0.1-0.5:1.

[0012] More preferably, the mass ratio of sodium alginate, water-soluble phosphate, purification factor and magnetic particles is 0.5-1.5:0.3-1:0.1-0.5:1.

[0013] Most preferably, the mass ratio of sodium alginate, water-soluble phosphate, purification factor and magnetic particles is 0.8-1:0.6-0.7:0.1-0.2:1.

[0014] Preferably, in solution B, the mass ratio of chitosan to calcium chloride is 0.5-1.5:1.

[0015] More preferably, the mass ratio of chitosan to calcium chloride is 0.8 to 1:1.

[0016] Preferably, the mixed solution A is dripped into the solution B at a molar ratio of calcium chloride to water-soluble phosphate of 0.5 to 1.5:1, more preferably at a molar ratio of calcium chloride to water-soluble phosphate of 0.7 to 1:1.

[0017] Preferably, after the mixed solution A is added dropwise, it is allowed to stand for 0.5 to 2 hours.

[0018] Preferably, in the mixed solution A, the concentration of the magnetic particles is 1-50 g / L.

[0019] More preferably, the concentration of the magnetic particles is 10 to 30 g / L;

[0020] Preferably, in solution B, the concentration of chitosan is 1 to 30 g / L. More preferably, the concentration of chitosan is 5 to 15 g / L.

[0021] Preferably, the water-soluble phosphate is sodium phosphate, potassium phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate.

[0022] Preferably, the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution are mixed uniformly according to the mass ratio of the magnetic particles, silicon and glycerol of 1:0.1-0.5:10-20.

[0023] Preferably, the polyallylamine is added at a molar ratio of polyallylamine to silicon of 0.001 to 0.005:1.

[0024] Preferably, after the polyallylamine is added, the reaction is carried out for 10 to 30 minutes.

[0025] Preferably, the silicon dioxide precursor solution is obtained by mixing tetramethoxysilane with an acid solution.

[0026] More preferably, the usage ratio of tetramethoxysilane to the acid solution is 1-2:10 g / ml.

[0027] More preferably, the acid solution is a hydrochloric acid solution or a sulfuric acid solution with a concentration of 0.5 to 5 mmol / L.

[0028] Preferably, the concentration of glycerol in the acidic buffer solution is 50 to 200 g / L. More preferably, the concentration of glycerol is 80 to 150 g / L.

[0029] Preferably, the pH of the acidic buffer solution is 6 to 6.8.

[0030] Preferably, the magnetic particles are magnetic nanoparticles.

[0031] Preferably, the purifying factor is a biological enzyme or a protein.

[0032] More preferably, the biological enzyme is urate oxidase.

[0033] The filler for hemoperfusion device is prepared according to the above method.

[0034] Beneficial effects of the present invention:

[0035] 1. Compared with the existing silica-alginate microcapsules, the dual biomimetic mineralization method of the present invention can retain the maximum activity of the purification factor.

[0036] 2. A loose network structure is formed during the biomineralization process, which provides sufficient channels for the diffusion of pathogenic factors in the blood, and provides a larger effective contact area and longer contact time for the purification factors and pathogenic factors, thereby improving the efficiency of the purification factors in removing pathogenic factors.

[0037] 3. The filler matrix for the hemoperfusion device of the present invention is formed by biomineralization, has good biocompatibility, can effectively reduce thrombosis, and reduces the risk of thrombosis in patients.

[0038] 4. Compared with macroporous resins and activated carbon that rely on their own adsorption, the filler matrix for the blood perfusion device of the present invention has no macroporous structure, which can greatly reduce the nonspecific adsorption of other substances in the blood that exist in the macroporous resin and activated carbon matrix, and the hemodynamics is more stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a schematic diagram of the structure of the filler for preparing the hemoperfusion device by dual biomineralization according to the present invention, wherein I is magnetic particles, II is sodium alginate-chitosan-calcium phosphate mineralization layer, and III is silicon dioxide mineralization layer.

[0040] Figure 2Schematic diagram of the experimental device for purifying uric acid by blood perfusion, wherein 1-blood perfusion device, 2-filler, 3-plasma bag before perfusion, 4-plasma bag after perfusion, 5-peristaltic pump. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is further described in detail below in conjunction with embodiments.

[0042] The method for preparing fillers for hemoperfusion devices by dual biomineralization of the present invention comprises the following steps:

[0043] (1) Primary biomineralization: preparing a mixed solution A containing sodium alginate, water-soluble phosphate, purification factor and magnetic particles, and a solution B containing chitosan and calcium chloride, and then dropping the mixed solution A into the solution B to obtain biomineralized magnetic capsule particles;

[0044] (2) Secondary biomineralization: preparing a silica precursor solution and an acidic buffer solution containing glycerol, then mixing the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution, and then adding polyallylamine to react to obtain the filler for the hemoperfusion device.

[0045] In a biomineralization process, sodium alginate solidifies into a gel under the action of calcium ions. At the same time, the phosphate ions produced by the ionization of water-soluble phosphate react with calcium ions to form calcium phosphate salts, forming a bionic mineralization layer that compositely encapsulates the purification factor. Chitosan protects the activity of the purification factor from being affected during the above-mentioned mineralization reaction.

[0046] In the secondary biomineralization process, the added glycerol is used as a protective agent to protect the activity of the purification factor from being affected during the reaction process, and the added polyallylamine is used as a biomineralization inducer to induce the silica precursor to form a SiO2 bionic mineralization layer.

[0047] In some preferred embodiments of the present invention, in the mixed solution A, the mass ratio of sodium alginate to magnetic particles can be controlled at 0.1-2:1, specifically 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.89:1, 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, and 2:1.

[0048] In some preferred embodiments of the present invention, in the mixed solution A, the mass ratio of the water-soluble phosphate and the magnetic particles can be controlled at 0.1-2:1, specifically such as 0.1:1, 0.2:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1, 0.55:1, 0.6:1, 0.62:1, 0.63:1, 0.64:1, 0.66:1, 0.68:1, 0.7:1, 0.75:1, 0.8:1, 0.85:1, 0.9:1, 0.95:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, and 2:1.

[0049] In some preferred embodiments of the present invention, in the mixed solution A, the mass ratio of the purification factor and the magnetic particles can be controlled at 0.1-0.5:1, specifically 0.1:1, 0.12:1, 0.13:1, 0.14:1, 0.15:1, 0.16:1, 0.17:1, 0.18:1, 0.19:1, 0.2:1, 0.24:1, 0.28:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, and 0.5:1.

[0050] In some preferred embodiments of the present invention, in solution B, the mass ratio of chitosan to calcium chloride can be controlled at 0.5-1.5:1, specifically such as 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.75:1, 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1, 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.4:1, and 1.5:1.

[0051] In some preferred embodiments of the present invention, the molar ratio of calcium chloride to water-soluble phosphate is 0.5 to 1.5:1, specifically 0.5:1, 0.55:1, 0.6:1, 0.65:1, 0.7:1, 0.71:1, 0.72:1, 0.73:1, 0.74:1, 0.75:1, 0.76:1, 0.77:1, 0.78:1, 0.79:1, 0.8:1, 0.82:1, 0.84:1, 0.86:1, 0.88:1, 0.9:1, 0.92:1, 0.94:1, 0.96:1, 0.98:1, 1:1, 1.05:1, 1.1:1, 1.15:1, 1.2:1, 1.25:1, 1.3:1, 1.35:1, 1.4:1, 1.5:1, drop the mixed solution A into the solution B.

[0052] In some preferred embodiments of the present invention, after the dropwise addition of the mixed solution A in step (1) is completed, the mixture is allowed to stand for 0.5 to 2 h, specifically 0.5 h, 0.6 h, 0.7 h, 0.8 h, 0.9 h, 1 h, 1.1 h, 1.5 h, 1.8 h, and 2 h.

[0053] In some preferred embodiments of the present invention, the concentration of magnetic particles in the mixed solution A can be controlled at 1-50 g / L, specifically such as 1 g / L, 2 g / L, 4 g / L, 6 g / L, 8 g / L, 10 g / L, 12 g / L, 14 g / L, 16 g / L, 18 g / L, 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L, 30 g / L, 34 g / L, 38 g / L, 40 g / L, 44 g / L, 46 g / L, and 50 g / L.

[0054] In some preferred embodiments of the present invention, in solution B, the concentration of chitosan can be controlled at 1-30 g / L, specifically such as 1 g / L, 2 g / L, 4 g / L, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, 10 g / L, 11 g / L, 12 g / L, 13 g / L, 14 g / L, 15 g / L, 16 g / L, 18 g / L, 20 g / L, 22 g / L, 24 g / L, 26 g / L, 28 g / L, and 30 g / L.

[0055] In some preferred embodiments of the present invention, the water-soluble phosphate can be selected from sodium phosphate, potassium phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate.

[0056] In order to reduce the effect of pH on the activity of the purifying factor, the water-soluble phosphate can be selected from disodium hydrogen phosphate or dipotassium hydrogen phosphate which has a certain pH buffering effect.

[0057] In some preferred embodiments of the present invention, in step (2), when the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution are mixed, the mass ratio of the magnetic particles to the silicon can be controlled at 1:0.1 to 0.5, specifically 1:0.1, 1:0.12, 1:0.14, 1:0.16, 1:0.18, 1:0.2, 1:0.22, 1:0.24, 1:0.26, 1:0.28, 1:0.3, 1:0.32, 1:0.34, 1:0.36, 1:0.38, 1:0.4, 1:0.42, 1:0.44, 1:0.46, 1:0.48, 1:0.5. The mass ratio of magnetic particles to glycerol can be controlled at 1:10-20, specifically 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, 1:16, 1:17, 1:18, 1:19, 1:20.

[0058] In some preferred embodiments of the present invention, in step (2), when polyallylamine is added, the molar ratio of polyallylamine to silicon can be controlled within the range of 0.001 to 0.005:1, specifically, 0.001:1, 0.002:1, 0.003:1, 0.004:1, 0.005:1.

[0059] In some preferred embodiments of the present invention, after the addition of polyallylamine is completed, the reaction time can be controlled within 10 to 30 minutes, such as 10 minutes, 15 minutes, 20 minutes, 25 minutes, or 30 minutes.

[0060] The silicon dioxide precursor solution can be obtained by acid hydrolysis of tetraalkoxysilane or sodium silicate, such as tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane.

[0061] In some preferred embodiments of the present invention, the silicon dioxide precursor solution is obtained by mixing tetramethoxysilane with an acid solution.

[0062] In some preferred embodiments of the present invention, the dosage ratio of tetramethoxysilane to acid solution can be controlled at 1 to 2:10 g / ml, specifically 1:10 g / ml, 1.2:10 g / ml, 1.3:10 g / ml, 1.4:10 g / ml, 1.5:10 g / ml, 1.6:10 g / ml, 1.7:10 g / ml, 1.8:10 g / ml, 1.9:10 g / ml, and 2:10 g / ml.

[0063] In some preferred embodiments of the present invention, the acid solution can be hydrochloric acid solution or sulfuric acid solution, and the concentration can be controlled at 0.5-5mmol / L, specifically 0.5mmol / L, 1mmol / L, 1.5mmol / L, 2mmol / L, 2.5mmol / L, 3mmol / L, 3.5mmol / L, 4mmol / L, 4.5mmol / L, 5mmol / L.

[0064] The acidic buffer solution containing glycerol can be obtained by mixing glycerol with the acidic buffer solution.

[0065] In some preferred embodiments of the present invention, the concentration of glycerol in the acidic buffer solution can be controlled at 50-200 g / L, specifically such as 50 g / L, 60 g / L, 70 g / L, 80 g / L, 90 g / L, 100 g / L, 110 g / L, 120 g / L, 130 g / L, 140 g / L, 150 g / L, 160 g / L, 170 g / L, 180 g / L, 190 g / L, and 200 g / L.

[0066] In some preferred embodiments of the present invention, the pH value of the acidic buffer solution can be controlled at 6 to 6.8.

[0067] In some preferred embodiments of the present invention, the acidic buffer solution may be a phosphate buffer.

[0068] In some preferred embodiments of the present invention, the (Fe3O4) magnetic particles are magnetic nanoparticles.

[0069] The magnetic particles (Fe3O4) can be prepared on the spot by conventional methods.

[0070] Using magnetic particles as cores can, on the one hand, improve the success rate of embedding and reduce the probability of forming non-embedded alginate gel impurity particles. On the other hand, a magnetic separator can be used to separate and screen the magnetic particles of immobilized enzymes and remove impurity particles without immobilized enzymes.

[0071] Example 1 Urate oxidase has a rapid oxidative decomposition effect on uric acid, and using it as a purification factor to prepare a filler for a hemoperfusion device

[0072] (1) Magnetic Nanoparticles

[0073] Take 4g FeCl2·4H2O and 10.8g FeCl3·6H2O and dissolve them in 200ml deionized water until fully dissolved. Then, stir magnetically at 2400rpm at room temperature, and add 150ml 29% NH4OH (ammonia monohydrate) at a rate of 1ml / min during stirring. After the addition is complete, let it stand for 30min, filter out the precipitate, and heat it in a water bath at 80℃ for 45min. After the reaction is completed, wash the product with deionized water and 95% ethanol 3 times each. Then suspend the obtained magnetic nanoparticles in 400ml of 95% ethanol and store at 4℃ for later use.

[0074] (2) Primary biomineralization

[0075] Sodium alginate was added to 100 ml of disodium hydrogen phosphate solution (100 mM) to obtain a mixed solution (sodium alginate concentration was 20 g / L), and then 2.25 g of magnetic nanoparticles and 0.3 g of uricase were added and stirred to obtain a mixed solution A.

[0076] Chitosan was added into 75 ml of calcium chloride solution (100 mM) to obtain solution B (chitosan concentration was 10 g / L).

[0077] Using a 5 ml syringe with a 0.9 mm syringe needle, the mixed solution A was added dropwise into the solution B, and after all the drops were added, the mixture was allowed to stand for 1 hour. The product was filtered out and washed with deionized water for 3 times to obtain sodium alginate-chitosan-calcium phosphate biomineralized magnetic capsule particles.

[0078] (3) Secondary biomineralization

[0079] Solution C was obtained by adding 1.52 g of tetramethoxysilane to 10 ml of freshly prepared 1 mM HCl at room temperature.

[0080] Glycerol was added to 350 ml of phosphate buffer solution with pH = 6.8 to obtain a solution with a glycerol concentration of 100 g / L, and then the above solution C and the biomineralized magnetic capsule particles obtained in step (2) were added to the solution. After fully shaking, 20 ml of 1 mM polyallylamine (CAS: 30551-89-4) was added and the reaction was oscillated at room temperature for 20 minutes. After the reaction was completed, the product was collected by a magnetic separator, washed with water 3 times and then vacuum dried to obtain a filler for a blood perfusion device that can specifically remove uric acid in the blood, with a structure such as Figure 1 shown.

[0081] Comparative Example 1

[0082] The preparation of the filler is compared with that of Example 1, except that disodium hydrogen phosphate is not added in the primary biomineralization of step (2).

[0083] Comparative Example 2

[0084] The preparation of the filler is compared with that of Example 1, except that chitosan is not added in the primary biomineralization of step (2).

[0085] Comparative Example 3

[0086] The preparation of the filler is different from that of Example 1, except that glycerol is not added in the secondary biomineralization in step (3).

[0087] Comparative Example 4

[0088] The preparation of the filler is compared with that of Example 1, except that no polyallylamine is added in the secondary biomineralization in step (3).

[0089] like Figure 2 The experimental device was built as shown, the filler prepared above was loaded into the hemoperfusion device, and the uric acid perfusion purification effect was tested with plasma. The results are as follows:

[0090] Uric acid level in the blood Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Before perfusion, μmol / L 488.5 463.2 502.5 459.3 511.0 After perfusion, μmol / L 220.6 443.0 268.7 271.8 359.4 Removal rate, % 54.8 4.3 46.5 40.8 29.7

[0091] Test conditions: 50 g filler, blood flow rate 100 ml / min, temperature 37°C.

[0092] Example 2

[0093] (1) Magnetic Nanoparticles

[0094] Take 4g FeCl2·4H2O and 10.8g FeCl3·6H2O and dissolve them in 200ml deionized water until fully dissolved. Then, stir magnetically at 2400rpm at room temperature, and add 150ml 29% NH4OH (ammonia monohydrate) at a rate of 1ml / min during stirring. After the addition is complete, let it stand for 30min, filter out the precipitate, and heat it in a water bath at 80℃ for 45min. After the reaction is completed, wash the product with deionized water and 95% ethanol 3 times each. Then suspend the obtained magnetic nanoparticles in 400ml of 95% ethanol and store at 4℃ for later use.

[0095] (2) Primary biomineralization

[0096] Sodium alginate was added to 100 ml of disodium hydrogen phosphate solution (100 mM) to obtain a mixed solution (sodium alginate concentration was 20 g / L), and then 2 g of magnetic nanoparticles and 0.3 g of uricase were added and stirred to obtain a mixed solution A.

[0097] Chitosan was added into 75 ml of calcium chloride solution (100 mM) to obtain solution B (chitosan concentration was 11 g / L).

[0098] Using a 5 ml syringe with a 0.9 mm syringe needle, the mixed solution A was added dropwise into the solution B, and after all the drops were added, the mixture was allowed to stand for 1 hour. The product was filtered out and washed with deionized water for 3 times to obtain sodium alginate-chitosan-calcium phosphate biomineralized magnetic capsule particles.

[0099] (3) Secondary biomineralization

[0100] Solution C was obtained by adding 3 g of tetramethoxysilane to 10 ml of freshly prepared 1 mM HCl at room temperature.

[0101] Glycerol was added to 350 ml of phosphate buffer solution with pH = 6.8 to obtain a solution with a glycerol concentration of 60 g / L, and then the above solution C and the biomineralized magnetic capsule particles obtained in step (2) were all added to the solution. After fully shaking, 20 ml of 1 mM polyallylamine (CAS: 30551-89-4) was added and the reaction was oscillated at room temperature for 20 minutes. After the reaction was completed, the product was collected by a magnetic separator, washed with water 3 times and then vacuum dried to obtain a filler for a hemoperfusion device that can specifically remove uric acid in the blood.

[0102] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a filler for a hemoperfusion device by dual biomineralization, comprising: (1) Primary biomineralization: preparing a mixed solution A containing sodium alginate, water-soluble phosphate, purification factor and magnetic particles, and a solution B containing chitosan and calcium chloride, and then dropping the mixed solution A into the solution B to obtain biomineralized magnetic capsule particles; (2) Secondary biomineralization: preparing a silica precursor solution and an acidic buffer solution containing glycerol, then mixing the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution, and then adding polyallylamine to react to obtain the filler for the hemoperfusion device; The purification factor is a biological enzyme or protein.

2. The method according to claim 1, characterized in that: In the mixed solution A, the mass ratio of sodium alginate, water-soluble phosphate, purification factor and magnetic particles is 0.1-2:0.1-2:0.1-0.5:1; In solution B, the mass ratio of chitosan to calcium chloride is 0.5-1.5:1; The mixed solution A is dropped into the solution B at a molar ratio of calcium chloride to water-soluble phosphate of 0.5 to 1.5:

1.

3. The method according to claim 2, characterized in that: The mass ratio of sodium alginate, water-soluble phosphate, purification factor and magnetic particles is 0.5-1.5:0.3-1:0.1-0.5:

1.

4. The method according to claim 3, characterized in that: The mass ratio of sodium alginate, water-soluble phosphate, purification factor and magnetic particles is 0.8-1:0.6-0.7:0.1-0.2:

1.

5. The method according to claim 2, characterized in that: The mass ratio of chitosan to calcium chloride is 0.8-1:

1.

6. The method according to claim 2, characterized in that: The mixed solution A is dropped into the solution B at a molar ratio of calcium chloride to water-soluble phosphate of 0.7 to 1:

1.

7. The method according to claim 6, characterized in that: After the addition of mixed solution A is completed, let it stand for 0.5 to 2 hours.

8. The method according to claim 1, characterized in that: In the mixed solution A, the concentration of magnetic particles is 1 to 50 g / L; In solution B, the concentration of chitosan is 1 to 30 g / L.

9. The method according to claim 8, characterized in that: The concentration of magnetic particles is 10 to 30 g / L.

10. The method according to claim 8, characterized in that: The concentration of chitosan is 5-15 g / L.

11. The method according to claim 1, characterized in that: The water-soluble phosphate is sodium phosphate, potassium phosphate, sodium dihydrogen phosphate, potassium dihydrogen phosphate, disodium hydrogen phosphate or dipotassium hydrogen phosphate.

12. The method according to claim 1, characterized in that: According to the mass ratio of magnetic particles, silicon and glycerol of 1:0.1-0.5:10-20, the biomineralized magnetic capsule particles, the silica precursor solution and the acidic buffer solution are mixed; Polyallylamine is added at a molar ratio of polyallylamine to silicon of 0.001 to 0.005:

1.

13. The method according to claim 12, characterized in that: After the addition of polyallylamine is completed, the reaction is allowed to proceed for 10 to 30 minutes.

14. The method according to claim 12, characterized in that: The silicon dioxide precursor solution is obtained by mixing tetramethoxysilane with an acid solution.

15. The method according to claim 14, characterized in that: The dosage ratio of tetramethoxysilane to acid solution is 1-2:10 g / ml.

16. The method according to claim 15, characterized in that: The acid solution is a hydrochloric acid solution or a sulfuric acid solution with a concentration of 0.5 to 5 mmol / L.

17. The method according to claim 12, characterized in that: The concentration of glycerol in the acidic buffer solution is 50-200 g / L.

18. The method according to claim 17, characterized in that: The concentration of glycerol is 80-150 g / L.

19. The method according to claim 17, characterized in that: The pH of the acidic buffer solution is 6-6.

8.

20. The method according to claim 1, characterized in that: The magnetic particles are magnetic nanoparticles.

21. The method according to claim 1, characterized in that: The biological enzyme is urate oxidase.

22. A filler for a hemoperfusion device prepared by the method according to any one of claims 1 to 21.